Wheat-Thinopyrum Substitution Lines Imprint Compensation Both From Recipients and Donors - Lyu, Zhongfan; Hao, Yongchao; Chen, Liyang; Xu, Shoushen; Wang, Hongjin; Li, Mengyao; Ge, Wenyang; Hou, Bingqian; Cheng, Xinxin; Li, Xuefeng; Che, Naixiu; Zhen, Tianyue; et al. (Frontiers in Plant Science, 2022)
Even frequently used in wheat breeding, we still have insufficient understanding of the biology of the products via distant hybridization. Here, a transcriptomic analysis was performed for six Triticum aestivum-Thinopyrum elongatum substitution lines in comparison with the host plants. All of the six disomic substitution lines, showed much stronger “transcriptomic-shock” occurred on alien genomes with 57.43~69.22% genes changed expression level, but little on the recipient genome (2.19~8.97%). Genome-wide suppression of alien genes along chromosomes was observed with high proportion of down-regulated genes (39.69~48.21%). Oppositely, the wheat recipient showed genome-wide compensation with more up-regulated genes, occurring on all chromosomes but not limited on the homologous groups. Moreover, strong co-up-regulation of the orthologs between wheat and Thinopyrum sub-genomes were enriched in photosynthesis with predicted chloroplastic localization, which indicates the compensation happened not only on wheat host genomes but also on alien genomes.